Singularly perturbed implicit control law for linear time varying SISO systems. (13th January 2013) - Puga, S.; Bonilla, M.; Malabre, M.; Lozano, R.
SUMMARY This paper considers the problem of stabilizing a single‐input single‐output linear time varying system using a low order controller and a reference model. The closed loop is a linear singularly perturbed system with uniform asymptotic stability behavior. We calculate bounds ϵ ∈ (0, ϵ * ) as in Kokotović's book, such that the uniform asymptotic stability of the singularly perturbed system is guaranteed. We show how to design a control law such that the system dynamics is assigned by a Hurwitz polynomial with constant coefficients. Copyright © 2013 John Wiley & Sons, Ltd.